Criminal liability of corporations: the problem of guilt - Пивоваров, В. В.; Маковецька, В. В. (Theory and practice of jurisprudence, 2016)
Problem setting. Today there is a need to holding accountable corporations to criminal liability. There is a question among scientists about the criminal and legal status of the perpetrator and guilt of the corporation. Therefore it is essential to analyse concepts of the introduction criminal responsibility of legal entities. Recent research and publications analysis. It is known various scientists who were engaged in research of criminal liability of legal entities, such as O. Antonov, B. Volzhenkyn, S. Kelyna, N. Kuznetsova, N. Hutorova, I. Danshin, O. Dudorov etc. Paper objective. To analyse options of determining the corporation as a perpetrator and bring it to criminal liability. Paper main body. It is known a few approaches to legal regulation of the institute of criminal liability of legal entities. According to the first variant the legal entity is considered an autonomous perpetrator. The second approach is based on the recognition of a natural person as an only subject of crime. The legal entities is exposed only criminal and legal impact. The third approach provides administrative responsibility of legal entities. There is still a contentious issue about the guilt of legal entities. The guilt as a mental attitude to the offense denotes only individual behavior of a personality and it can not be mechanically transferred to the criminal activities of a legal entity. The guilt of a legal entities must be assessed as a mental attitude of natural persons-heads of a corporation to the action and its consequences. The main argument of opponents of the criminal liability of legal entities is that the action of the corporation cannot have psychological characteristic. That is why the question about the responsibility of the legal entity can put only in that case if it will be established the guilt of a chief this corporation. Conclusions of the research. Today is undoubted about the necessary to holding accountable legal entities for committing multitude economic, ecologic crimes, crimes against peace and security of mankind etc. The main obstacle introduction of criminal liability legal entities is that recognition the legal entity as perpetrator does not correspond with the traditional doctrine of criminal law. That is why must be improved as the institute of criminal responsibility legal entities and as national criminal law.